The value of the routine third trimester ultrasound scan in antenatal care: Problems with guidance and outdated data in a highly technological field. (February 2020) - Bakalis, Spyros; Cao, Kevin; Johal, Navroop; Cuckow, Peter; Pandya, Pranav
Abstract: Ultrasound scanning is a cornerstone of modern antenatal care, enabling the detection of fetal abnormalities such as congenital disease, chromosomal defects and growth-disorders as well as maternal diseases such as pre-eclampsia. As technology and techniques evolve, care paradigms and clinical guidance must be re-evaluated with current literature so as to provide expectant parents with the highest quality of care. We present here the current state of the literature, the conflict between guidance and research endeavours and present suggestions for future study.